Role of Quality Management System in Enhancing the Performance in Manufacturing Industries - Sivaramakrishnan, G; Giridhara, S (Ushus Journal of Business Management, 2017)
After globalization in the 1990s, the standardizationprocess in manufacturing industries has gainedmomentum. In this study, an attempt has been made to identify the role of Quality Management System (QMS) in enhancing performance in an Indian manufacturing industry, with M/S Ramdevs Motors, a pumps manufacturing industry, as the place of this study.Performance measures like, Increase in financial performance, productivity, etc. have been considered in this study. An opinion survey type questionnaire was used to collect data from the organization. The performance of the company before and after the implementation of QMS was collected, processed and analysed using statistical tools. The results of the studyreveal that the role of QMS has significance in enhancing the performance of the organization but has no significance in financial performance of the organization.